Zimbabweans and the South African Economy (The Strategic Review for Southern Africa, 2023)
“They do not want us in their country, yet we contribute significantly,” shared a Zimbabwean woman in the Cape Town region of South Africa. The economic turmoil in Zimbabwe has led to decades of immigration to South Africa with no clear resolution to migration in sight. Despite legal challenges and xenophobic backlash, Zimbabweans believe their impact on South Africa has been substantial. The authors engaged 56 Zimbabweans with a 30-question questionnaire covering basic demographic information, employment-related inquiries, financial and income-related matters. These were distributed among respondents from various socio-economic sectors. The research findings provide insights into Zimbabwean spending patterns and overall perspectives on living and working in South Africa. With this research and the study of recent court rulings in South Africa, the authors argue that despite the xenophobic atmosphere, Zimbabwean immigrants are contributing to the South African economy and the social fabric. Moreover, as the situation in Zimbabwe continues to deteriorate, South Africa looks to be their long-term place of residence. How South African handles Zimbabwean immigrants in the future offers an opportunity to reset current immigration policies and support economic growth in the region.